Que educação é pública? Análise preliminar do atendimento conveniado na educação infantil nas diferentes regiões administrativas brasileiras - Borghi, Raquel Fontes; Bertagna, Regiane Helena (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2016)
Abstract: This paper presents and discusses data about private subsidized service in early childhood education in Brazilian administrative regions. In addition to the bibliographical study on the subject, we used the data available at the National Fund for the Development of Education (FNDE) for 2013 to make a survey on the number of municipalities in each state of the Federation with private subsidized enrollments in child education. The aim was to discuss the role of the private sector in providing early childhood education. Results showed that the agreement policy based on public subvention to the private sector is more solid in the Southeast and South regions and point out to an urgent need of affirmative actions for a secular and high quality public education for all.

Resumo: Apresenta e discute dados referentes ao atendimento conveniado na educação infantil nas regiões administrativas brasileiras. Além do estudo bibliográfico sobre a temática, realizou-se um levantamento acerca do número de municípios brasileiros de cada estado da Federação com matrículas conveniadas de educação infantil por meio dos dados disponíveis no Fundo Nacional de Desenvolvimento da Educação (FNDE), referentes ao ano de 2013. O objetivo foi discutir a atuação do setor privado no atendimento da educação infantil. Os resultados evidenciam uma maior consolidação nas regiões Sudeste e Sul de uma política de conveniamento pautada em subsídios públicos ao setor privado e indicam a urgente necessidade de afirmação e luta por uma educação pública, laica e de qualidade para todos.
Which education is public? Preliminary analysis of private subsidized service in child education in different Brazilian administrative regions
Keywords: privatization; right to education; financing of education; privatização; direito à educação; financiamento da educação